CHANGING SOURCES OF MAGMA GENERATION BENEATH INTRA-OCEANIC ISLAND ARCS: AN INSIGHT FROM THE JUVENILE KOHISTAN ISLAND ARC, PAKISTAN HIMALAYA - Bignold S.M.; Treloar P.J.; Petford N. (My University, 2006)
The Kohistan arc, situated in the Pakistan Himalaya, is a Cretaceous intraoceanic island arc which was initiated during the northward movement of the Indian Plate. The arc was sutured to Asia at ca. 100 Ma. It was subsequently tilted northward when underplated by Indian continental crust during the early stages of India-Asia collision. Deep erosion of this tilted section provides a spectacular section through the whole arc sequence and offers a profound insight into the mechanisms of early stages of arc formation. Geochemical analysis and rare earth element modelling of basaltic sequences which date from the intraoceanic stages of arc development allow identification of three main magma source types in the mantle beneath the juvenile arc. The 'E-type' Kamila Amphibolites, with a MORB-type chemistry, form the intraoceanic basement to the arc. The 'D-type' Kamila Amphibolites are the earliest of the arc volcanic rocks. These were extracted from a primitive spinel-bearing mantle source, above a north-dipping subduction zone. The stratigraphically younger basalts of the Jaglot Group and Ghizar Formation of the Chalt Volcanic Group were derived from partial melting of a garnet-bearing source at greater depth. The Hunza Formation of the Chalt Volcanic Group contains the youngest mafic volcanic rocks of the intraoceanic arc. Although coeval with the Ghizar Formation of the Chalt Volcanic Group, they were generated by melting of a depleted, spinel-bearing mantle source rock and were erupted into a spatially and temporally restricted back-arc basin developed behind the volcanic front. The Chalt Volcanic Group was therefore formed from two different, adjacent, mantle source regions active at the same time. Results of REE modelling are consistent with models for intraoceanic arc formation in which the earliest volcanic rocks are derived from shallow level spinel-bearing peridotite, and later ones from a deeper garnet-bearing source. This is consistent with the melt region becoming deeper with time as subduction continues. A two-stage model is proposed for the back-arc basalts of the Hunza Formation in which a mantle source, depleted from a previous melting event, is underplated beneath the arc and later remelted during decompression as a consequence of extension and rifting of the arc. © 2006 Elsevier B.V. All rights reserved.
Keywords: GEOCHEMISTRY; KOHISTAN; RARE EARTH ELEMENT MODELLING; STRATIGRAPHY; SUBDUCTION; Мезозой::Меловая; Mesozoic::Cretaceous